Genomic sequencing identifies tuberculosis cluster in inner-city Sydney boarding house, Australia, 2022 - Stiboy, Eunice; Rigava, Standish; Katelaris, Anthea; Sheppeard, Vicky; Glynn-Robinson, Anna; Al-Hindawi, Yasmeen; Goldberg, Hazel; Shaw, Kerrie; Sintchenko, Vitali; Martinez, Elena; Crighton, Taryn; Donnan, Ellen; et al. (Western Pacific Surveillance and Response, 2025)
Objective: In 2022, the New South Wales TB Program was notified of genomically clustered Mycobacterium tuberculosis isolates from two smear-positive tuberculosis (TB) patients diagnosed 3 months apart. Secondary investigations found they resided in the same Sydney boarding house. The objective of this study was to investigate this cluster and conduct active case finding among contacts. Methods: We conducted a site visit to understand transmission risk, reviewed patient histories, performed a risk assessment and conducted on-site TB contact screening, including interferon-gamma release assay testing. Long-term residents were also screened via chest X-ray. Past residents were referred to local TB services. Results: Four residents with TB disease were identified, three of whom were genomically linked to the cluster. The exposure period in the boarding house was determined to be from January 2021 to September 2022. All residents and staff were considered contacts requiring screening. Of the 91 contacts identified, 37 (41%) completed screening, including 20 (22%) who attended the on-site clinic. Among those screened, one resident with TB disease (patient 4) and three residents and one staff member with TB infection were identified. Discussion: This cluster highlights the role of genomic sequencing in detecting TB transmission. The first three patients were infectious for prolonged periods before diagnosis, likely facilitating transmission in communal areas. In multidwelling buildings with TB exposures, contact screening of all residents may be required when prolonged exposures are found. Strategies to increase screening completion should be further explored.